2003
DOI: 10.1046/j.1523-1747.2003.12014.x
|View full text |Cite
|
Sign up to set email alerts
|

Fas Ligand in Pemphigus Sera Induces Keratinocyte Apoptosis through the Activation of Caspase-8

Abstract: The Fas/Fas ligand system triggers the extrinsic apoptotic pathway and is involved in several inflammatory conditions, also at the skin level. The Fas/Fas ligand cell death pathway plays a major role in anoikis, a type of apoptosis characterized by cell detachment. As pemphigus is characterized by loss of cell to cell adhesion, we evaluated the role of anoikis and Fas ligand in this bullous disease. We report that, in suprabasal epidermis from perilesional pemphigus skin, most keratinocytes are apoptotic. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 22 publications
8
116
1
6
Order By: Relevance
“…These observations are consistent with finding in most models of apoptosis that cell death begins 12 to 24 hours after an initial trigger 48 and that acantholysis develops Ͼ24 hours after exposure to PVIgG. 11,13,14 Puviani et al 10 observed that apoptosis can be enhanced in cells as Figure 6. Hypothetical scheme of the signaling mechanisms leading to acantholysis through predominantly oncotic and apoptotic pathways in PV-1 and PV-2 patients, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…These observations are consistent with finding in most models of apoptosis that cell death begins 12 to 24 hours after an initial trigger 48 and that acantholysis develops Ͼ24 hours after exposure to PVIgG. 11,13,14 Puviani et al 10 observed that apoptosis can be enhanced in cells as Figure 6. Hypothetical scheme of the signaling mechanisms leading to acantholysis through predominantly oncotic and apoptotic pathways in PV-1 and PV-2 patients, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…The group of affected genes included those encoding cytokines and cytokineinducible proteins, which is in keeping with observations that pemphigus antibodies can modulate the cytokine production in KC (93,94). Finally, changes of apoptosis-related genes may underlie the appearance of an apoptotic phenotype in KC prior to cell-cell detachment (acantholysis) in the skin of pemphigus patients (95). Evidence that keratinocyte apoptosis occurs in PV is growing (96 -98).…”
Section: Discussionmentioning
confidence: 58%
“…For example, keratinocytes treated with anti-Dsg1 antibody obtained from patients with PH, which is a typical infl ammatory pemphigus, secreted a seven-to nine-fold increase of IL-8 compared with the controls and expressed a higher intensity of cytoplasmic IL-8 staining, suggesting a functional role for IL-8 in the pathogenesis of the neutrophil-dominant subset of PH (O ' Toole et al, 2000). On the other hand, paraneoplastic pemphigus demonstrates histopathologically a satellite necrosis of epidermal keratinocytes attached with lymphocytes as shown in Figure 4, suggesting an involvement of PV-IgG activation of caspases, apoptotic pathways (Pelacho et al, 2004;Puviani et al, 2003;Wang et al, 2004). Furthermore, some of these PV-activated signaling pathways may be linked to activation of some proteases, such as metaraprotease, MMP-9 (Cirillo & Al-Jandan, 2013).…”
mentioning
confidence: 95%
“…In addition, PKC involvement in pemphigus appears to be now well accepted in terms of generation of weak-adhesive desmosome condition (Cirillo et al, 2010;Kitajima, 2013;Spindler & Waschke, 2014). Furthermore, it has been shown that apoptosis signaling may be involved in pemphigus pathogenesis (Pelacho et al, 2004;Puviani et al, 2003;Wang et al, 2004).…”
mentioning
confidence: 99%